SWOT ANALYSIS AND TOWS MATRIX E-GOVERNMENT ON TANA TIDUNG CITY OF KALIMANTAN UTARA - Rudy, Rudy; Prasetia, Abdul Muis (Elinvo (Electronics, Informatics, and Vocational Education), 2018)
ABSTRAct Information and Communication Technology (ICT) can improve the speed of information delivery, efficiency, global reach and transparency. One of the efforts to realize good corporate governance (GCG) governance in the era of regional autonomy is to use information and communication technology or popularly called e-Government. The implementation of e-Government the need for master plan information technology as a guide in the integration of information technology in Local Government, e-Government implementation is expected to help improve interaction between government, community and business, so as to encourage political and economic development. In this paper presents the determination of e-Government policy strategy using SWOT analysis method which is considered capable to analyze the relationship or interaction between internal elements, namely strengths and weaknesses, as well as against the external elements of opportunities and threats.Â Keywords: ICT, SWOT, e-Government.